2007
DOI: 10.2519/jospt.2007.2404
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Ankle Arthritis: An Update on Conservative and Surgical Management

Abstract: T he purpose of this manuscript is to provide current information regarding the examination, conservative treatment, and surgical treatment for individuals with posttraumatic arthritis. The 3 major categories of arthritis are inflammatory, osteoarthritis, and posttraumatic arthritis. Rheumatoid arthritis is the most common form of inflammatory arthritis; however, it does not always affect the ankle.35 It has been reported that 10% to 50% of individuals with rheumatoid arthritis have ankle involvement. 8,16,48,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 96 publications
0
22
0
1
Order By: Relevance
“…Mild to moderate ankle arthritis can often be managed with an ankle foot orthoses and a rocker-bottom shoe, provided that no significant varus/valgus deformity is present 2,4). Ankle arthrodesis and replacement are two common surgical treatment options for end-stage ankle osteoarthritis.…”
mentioning
confidence: 99%
“…Mild to moderate ankle arthritis can often be managed with an ankle foot orthoses and a rocker-bottom shoe, provided that no significant varus/valgus deformity is present 2,4). Ankle arthrodesis and replacement are two common surgical treatment options for end-stage ankle osteoarthritis.…”
mentioning
confidence: 99%
“…Uncorrectable deformities preclude this from happening and should not be considered for ankle replacement. Similarly, patients with active lifestyle interests that involve rapid acceleration and deceleration forces on the articulating surfaces will likely prematurely wear their ankle replacement [17,18,25]. In our study, six patients in B group and three patients in A group showed radiological evidence of degeneration of the talonavicular joint and the subtalar joint.…”
Section: Resultsmentioning
confidence: 69%
“…In our study, for older and less demanding end-stage ankle arthritis patients, a. total ankle arthroplasty is recommended. Whereas younger with a high activity level, no adjacent joint arthritis, and posttraumatic end-stage ankle arthritis, an arthrodesis is recommended [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attempted through the use of offloading strategies such as assistive devices [26]. A single point cane can decrease vertical loading by 11-25% [27,28].…”
Section: Nonmedicinal Treatment Choices In the Management Of Ankle Osmentioning
confidence: 99%